Flexible back-illuminated dye sensitised solar cells (DSSCs) with titanium dioxide/silver nanoparticles composite photoanode for improvement of power conversion efficiency - Shamsudin, N.H.; Shafie, S.; Ab Kadir, M.Z.A.; Ahmad, F.; Sulaiman, Y.; Chachuli, S.A.M.; Razali, M.C. (Elsevier BV, 2023)
With flexibility practices becoming a vital concern for dye sensitised solar cells (DSSCs) today, researchers are widely developing choices of excel conductivity and durable anode substrate, which is metal. As metals are exposed to light impenetrability caused by its opacity, the illumination sides were transitioned from the front-side to backside of the DSSCs. The less light absorption reduces the power conversion efficiency (PCE). The surface treatment was posited onto the titanium (Ti) substrate in promoting a gap for titanium dioxide (TiO2) during deposition, as well as discarding the oxide layer of the Ti surface. To improve the PCE for backside illumination DSSCs of Ti substrate, this paper proposes the embedment of silver nanoparticles (AgNPs) into TiO2 at various concentrations between 1.0 wt% and 3.0 wt%. The AgNPs were produced by solvothermal method in sizes of 23 nm, 25 nm, 29 nm, and 36 nm. The chosen size of 29 nm has been laid on the ultraviolet-visible (UV-Vis) and transmission electron microscopy (TEM) with the highest absorbance and low status of agglomeration. The back-illuminated AgNPs-TiO2 film acquired optimal PCE = 4.691%, Jsc = 10.0 mA/cm2, FF = 0.67, and Voc = 0.70 mV in response to the 2.0 wt% concentration of AgNPs-TiO2 deposited onto a flexible Ti substrate.